2010
DOI: 10.1364/ol.35.003607
|View full text |Cite
|
Sign up to set email alerts
|

Optical-feedback cavity-enhanced absorption spectroscopy with a quantum cascade laser

Abstract: Optical-feedback cavity-enhanced absorption spectroscopy is demonstrated in the mid-IR by using a quantum cascade laser (emitting at 4.46 μm). The laser linewidth reduction and frequency locking by selective optical feedback from the resonant cavity field turns out to be particularly advantageous in this spectral range: It allows strong cavity transmission, which compensates for low light sensitivity, especially when using room-temperature detectors. We obtain a noise equivalent absorption coefficient of 3 × 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(34 citation statements)
references
References 11 publications
2
31
0
Order By: Relevance
“…OFCEAS is a cavity enhanced absorption method alternative to CRDS (Morville et al, 2004;Maisons et al, 2010;Gagliardi and Loock, 2014), which has specific advantages for trace analysis Faïn et al, 2014;Desbois et al, 2014). This technique uses feedback of light from a high-finesse V-cavity to lock the laser emission over cavity resonances during a laser frequency scan.…”
Section: Ofceas At 3007 CM −1mentioning
confidence: 99%
“…OFCEAS is a cavity enhanced absorption method alternative to CRDS (Morville et al, 2004;Maisons et al, 2010;Gagliardi and Loock, 2014), which has specific advantages for trace analysis Faïn et al, 2014;Desbois et al, 2014). This technique uses feedback of light from a high-finesse V-cavity to lock the laser emission over cavity resonances during a laser frequency scan.…”
Section: Ofceas At 3007 CM −1mentioning
confidence: 99%
“…It has been demonstrated that this technique is compatible with different kinds of semiconductor lasers. Indeed, while OF-CEAS was previously developed in the NIR with distributed feedback telecom diode lasers (Morville et al, 2005;Kassi et al, 2006), it has been demonstrated that it is compatible with extended cavity diode lasers that operate in the visible (Courtillot et al, 2006;Horstjann et al, 2014) and with quantum cascade lasers (Maisons et al, 2010;Gorrotxategi-Carbajo et al, 2013) as well as more recently with interband cascade lasers (Manfred et al, 2015;Richard et al, 2016) in the mid-infrared region.…”
Section: Discussionmentioning
confidence: 99%
“…The performance of the OF-CEAS technique in the NIR led a private company (AP2E, Aix-en-Provence, France) to exploit the patent for commercially available analysers (namely Pro-CEAS). On the other hand, exploiting OF-CEAS in the MIR allows the reaching of sub-ppb levels for several species of interest in trace detection and ppm levels for isotopic ratio measurements (Maisons et al, 2010;Gorrotxategi-Carbajo et al, 2013;Manfred et al, 2016;Richard et al, 2016).…”
Section: Ventrillard Et Al: Comparison Of Of-ceas and Gcmentioning
confidence: 99%
“…The two next sections present for each of the two spectral points, the experimental setups, spectra acquired, the continuum OFCEAS is a cavity enhanced absorption method alternative to CRDS (Morville et al, 2004;Romanini et al, 2006;Maisons et al, 2010;Gagliardi and Loock, 2014) which has specific advantages, in particular for trace detection analysis Faïn et al 2014;Desbois et al 2014). This technique uses feedback of light from a high-finesse V-cavity to lock the 25 laser emission over cavity resonances during a laser frequency scan.…”
Section: Introductionmentioning
confidence: 99%